Integrating 3D-Printed and Natural Staghorn Coral (Acropora cervicornis) Restoration Enhances Fish Assemblages and Their Ecological Functions - Edwin A. Hernández-Delgado; Jaime S. Fonseca-Miranda; Alex E. Mercado-Molina; Samuel E. Suleimán-Ramos (Diversity, 2025)
Coral restoration is essential for recovering depleted populations and reef ecological functions. However, its effect on enhancing fish assemblages remains understudied. This study investigated the integration of 3D-printed and natural Staghorn coral (Acropora cervicornis) out-planting to assess their role in enhancing benthic spatial complexity and attracting fish communities. Conducted between 2021 and 2023 at Culebra Island, Puerto Rico, we employed a before-after-control-impact (BACI) design to test four treatments: natural A. cervicornis, 3D-printed corals, mixed stands of 3D-printed and natural corals, and non-restored controls. Fish assemblages were monitored through stationary counts. Results showed that integrating 3D-printed and natural corals enhanced fish assemblages and their ecological functions. Significant temporal changes in fish community structure and biodiversity metrics were observed, influenced by treatment and location. Herbivore abundance and biomass increased over time, especially in live coral and 3D-printed plots. Reefs with higher rugosity exhibited greater Scarid abundance and biomass post-restoration. Piscivore abundance also rose significantly over time, notably at Tampico site. Fishery-targeted species density and biomass increased, particularly in areas with live and 3D-printed coral out-plants. Fish assemblages became more complex and diverse post-restoration, especially at Tampico, which supported greater habitat complexity. Before restoration, fish assemblages showed a disturbed status, with biomass k-dominance curves above abundance curves. Post-out-planting, this trend reversed. Control sites showed no significant changes. The study demonstrates that restoring fast-growing branching corals, alongside 3D-printed structures, leads to rapid increases in abundance and biomass of key fishery species, suggesting its potential role promoting faster ecosystem recovery and enhanced coral demographic performance.